Moderation, Pandemics and The Era of Disruption: Strengthening Literacy Religious in Urban Millennials After The Outbreak Of Covid-19 - Yasin, Muhamad; Khasbulloh, M. Nabil (Didaktika Religia, 2022)
This study will examine solutions to strengthen moderate religious literacy among millennials after the outbreak of Covid-19 in the era of disruption with the following research focus: Improving skills to strengthen the religious literacy of urban millennials after the outbreak of Covid-19; Explaining the contribution of these skills in improving religious moderation for urban millennials after the outbreak of Covid-19. This study uses a phenomenological qualitative approach. Data was collected using the method of participant observation and independent interview, so that this research is done in-depth, intensively, and in detail on the phenomenon that occurs. Data was analyzed by reducing, displaying, inference, and verification of data. To test the validity of the data, credibility, transferability, dependability, and confirmability are carried out. This study reveal that to strengthen millennial religious literacy means equipping students with the knowledge and skills to understand and discuss religions and issues around them confidently, accurately, critically through reflection, inquiry, empathy, analysis and evaluation skills, reasoning, synthesis, and communication. That way students will understand that a friendly, peaceful, friendly, tolerant, flexible, and inclusive face is the face of Islam in the framework of moderation. Contributions of religious literacy strategies in improving religious moderation, namely as follows: First, form mental adjustment and critical in understanding various religious content; Second, being able to identify differences in beliefs, and practice the teachings of Islam in the community; Third, have a preventive spirit from hate speech wrapped in religious content.